Analisis Penerapan PSAK 71 pada Perusahaan Pembiayaan: Studi pada Perusahaan Pembiayaan di Jabodetabek - Respati, Herry (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The obligation to utilize PSAK 71 on the funding company has triggered some debates. One of the debates occurred due to the concern of funding companies since PSAK 71 will potentially cut the companies' profit. This happened due to the forward-looking system that PSAK 71 applied for the funding companies, including obligations for funding companies to provide reserve funds and other supports. Moreover, various issues regarding macro-economy considerations related to the funding company exist. However, in the long term, PSAK 71 has the potential to guarantee sustainable companies’ capital when it is facing global economic uncertainty.